Impaired retinal vasodilator responses in prediabetes and type 2 diabetes. (7th June 2013) - Lott, Mary E. J.; Slocomb, Julia E.; Shivkumar, Vikram; Smith, Bruce; Quillen, David; Gabbay, Robert A.; Gardner, Thomas W.; Bettermann, Kerstin
Abstract: Purpose:  In diabetes, endothelial dysfunction and subsequent structural damage to blood vessels can lead to heart attacks, retinopathy and strokes. However, it is unclear whether prediabetic subjects exhibit microvascular dysfunction indicating early stages of arteriosclerosis and vascular risk. The purpose of this study was to examine whether retinal reactivity may be impaired early in the hyperglycaemic continuum and may be associated with markers of inflammation. Methods:  Individuals with prediabetes ( n  = 22), type 2 diabetes ( n  = 25) and healthy age and body composition matched controls ( n  = 19) were studied. We used the Dynamic Vessel Analyzer to assess retinal vasoreactivity (percentage change in vessel diameter) during a flickering light stimulation. Fasting highly sensitive c‐reactive protein (hs‐CRP), a marker of inflammation, was measured in blood plasma. Results:  Prediabetic and diabetic individuals had attenuated peak vasodilator and relative amplitude changes in retinal vein diameters to the flickering light stimulus compared with healthy controls (peak dilation: prediabetic subjects 3.3 ± 1.8%, diabetic subjects 3.3 ± 2.1% and controls 5.6 ± 2.6%, p = 0.001; relative amplitude: prediabetic subjects 4.3 ± 2.2%, diabetic subjects 5.0 ± 2.6% and control subjects 7.2 ± 3.2%, p = 0.003). Similar findings were observed in retinal arteries. Levels of hs‐CRP were not associated with either retinal vessel response parameters. Conclusion:  Retinal reactivity was impaired in prediabetic and type 2 diabetic individuals in parallel with reduced insulin sensitivity but not associated with levels of hs‐CRP. Retinal vasoreactivity measurements may be a sensitive tool to assess early vascular risk.